2005
DOI: 10.1111/j.1469-7580.2005.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes and NG2‐glia: what's in a name?

Abstract: Classic studies recognize two functionally segregated macroglial cell types in the central nervous system (CNS), namely astrocytes and oligodendrocytes. A third macroglial cell type has now been identified by its specific expression of the NG2 chondroitin sulphate proteoglycan (NG2-glia). These NG2-glia exist abundantly in both grey and white matter of the mature CNS and are almost as numerous as astrocytes. It is well established that NG2-glia give rise to oligodendrocytes. However, the majority of NG2-glia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
89
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 32 publications
0
89
2
1
Order By: Relevance
“…In addition, although retaining a much higher number of radial glial cells in the adult telencephalon, the characteristic stellate-shaped astrocytes known from the mammalian brain could so far not be identified in the zebrafish telencephalon (Mä rz et al, 2010). The OPCs in the zebrafish telencephalon may thus compensate for this by having taken up functions that astrocytes in the mammalian brain carry out (Nishiyama et al, 2005) or radial glia-like cells subserve these astrocytic functions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, although retaining a much higher number of radial glial cells in the adult telencephalon, the characteristic stellate-shaped astrocytes known from the mammalian brain could so far not be identified in the zebrafish telencephalon (Mä rz et al, 2010). The OPCs in the zebrafish telencephalon may thus compensate for this by having taken up functions that astrocytes in the mammalian brain carry out (Nishiyama et al, 2005) or radial glia-like cells subserve these astrocytic functions.…”
Section: Resultsmentioning
confidence: 99%
“…Despite common remarks in the literature that the human brain contains 100 billion neurons and 10-to 50-fold more glial cells (e.g., [57][58][59], no references are given to support these statements; to the best of my knowledge, they are none other than ballpark estimates (60). Comparing the human brain with other mammalian brains thus required first estimating the total numbers of neuronal and nonneuronal cells that compose these brains, which we did a few years ago (25).…”
Section: Human Brain As a Scaled-up Primate Brainmentioning
confidence: 99%
“…Even so, they lack expression of most differentiated glial celltype specific markers (12). Indeed, based on these observations, several studies have suggested that the majority of postnatal NG2ϩ synantocytes comprise an independent neuroepithelial lineage distinct from neurons, astrocytes, and oligodendrocytes (4,12,14), a proposal that has provoked ongoing debate (15,16).…”
mentioning
confidence: 99%